ALTERNATIF BAHAN DAN PERBAIKAN KODIFIKASI POLA SEPATU DI CV BAROKAH SURABAYA, JAWA TIMUR - Ainu Rakhma Fatkhia; Rofiatun Nafiah (Politeknik ATK Yogyakarta, 2019)
The stunted of shoe production in CV Barokah is identified in the shoe pattern section. The company has to make shoe pattern repeatedly because pattern materials are not durable. Uncompleted pattern codification also creates problems in shoe production. This research aims to give solutions for shoe pattern problems in the company with material improvement and pattern codification. The material observed is the process of making shoes, especially focusing on material and pattern codification. Data collection methods are observation and documentation. This research uses experiment method in order to solve the problem. The results of problem solving can be concluded that patterns made of cardboard, manila paper, cardboard, and texon are more easily damaged when compared to patterns made from mica. In addition, the complete codification must include the name of pattern, size, in/out sign, center sign, balance sign, elasticity, accessory sign, lodging sign, and amount of pattern. Completing shoe pattern codification also makes shoe production become more efficient.